Spectral Wave-Driven Bedload Transport Across a Coral Reef Flat/Lagoon Complex - Rosenberger, Kurt J.; Storlazzi, Curt D.; Cheriton, Olivia M.; Pomeroy, Andrew W. M.; Hansen, Jeff E.; Lowe, Ryan J.; Buckley, Mark L. (Frontiers in Marine Science, 2020)
Coral reefs are an important source of sediment for reef-lined coasts and help to maintain beaches by providing protection though dissipation of wave energy. Understanding the mechanisms that deliver sediment to the coast from coral reefs and quantifying the total volume of sediment generated at coral reefs are critical for projecting future coastal change. A month-long hydrodynamics and sediment transport study on a fringing reef/lagoon complex in Western Australia indicates that lower frequency wave energy constituents are important to the total bedload transport of sediment across the reef flat and lagoon to the shoreline. The reef flat and the lagoon are characterized by distinctly different transport regimes, resulting in an offset in the timing of bedform migration between the two. Short-term storage of sediment occurs on the reef flat, which is subsequently transported into the lagoon when offshore wave heights increase and strong currents due to wave breaking at the reef crest develop. This sudden influx of sediment is correlated with an increase in bedform migration rates in the lagoon. Infragravity wave energy on the reef flat and lagoon make an important contribution to the migration of bedforms and resultant bedload transport. Given the complexity of the hydrodynamics of fringing reefs, the transfer of energy to lower frequency bands, as well as accurate estimates of sources and sinks of sediment, must but considered in order to correctly model the transport of sediment from the reef to the coast.